ANALISIS PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, OPERATING CYCLE, LEVERAGE, DAN PERTUMBUHAN PENJUALAN TERHADAP JUMLAH MODAL KERJA (Studi Kasus Pada Perusahaan Food and Beverages Yang Terdaftar Di Bursa Efek Indonesia Periode 2007-2010) - Megarifera, Livia Nadya Megarifera; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2013)
The amount of working capital through WCR in food and beverage companies experiencedsignificant changes over period 2007-2010. Working capital is important area in financial management because it refers to the availability of the net current assets of the business for its operations. Working capital reflects the management of short-term assets and liabilities of the firms with the maturities of less than a year. Continuous monitoring is required to maintain optimum levels of various components of working capital. This study aims to analyze the factors that influence toward the amount of working capital.The population in this research is taken from food and beverage companies which enlisted in the BEI from year 2007-2010. The samples are obtained by using the purposive samplingmethod until only 16 companies left to be taken as samples in this research. This research usesregression analysis method to find the effect of independent variables (determining factors) of the working capital, such as size, profitability, operating cycle, leverage, and company’s sales growth.Based  on  the  results  of  regression  analysis  for  the  five  independent  variables,  onlyleverage and sales growth that have a significant effect on the amount of working capital. While the size, profitability and operating cycle have not significant effect on the amount of working capital in food and beverage companies sector which enlisted in the BEI from year 2007 -2010.